Draft Annual Plan 1978-1979 (Sectoral Plans) Government of Nagaland - Government of Nagaland (Government of Nagaland, 1977)
The Nagaland Draft Annual Plan 1978–79 outlines a comprehensive sectoral development strategy emphasizing agricultural expansion, infrastructure strengthening, socio-economic transformation, and employment generation. A major thrust has been placed on agriculture and minor irrigation, with substantial increases in financial outlays to support land reclamation, land development, terracing of hill areas, and enhanced irrigation potential. The plan proposes mechanization through procurement of bulldozers, increased subsidies for terracing, and integration with Small Farmers Development Agency (SFDA) programmes to benefit small and marginal farmers. Minor irrigation allocations have been significantly enhanced to complement expanded land development, targeting increased irrigation coverage through lift irrigation and diversion channels. The cooperation sector is being restructured through the establishment of Large Area Multi-Purpose Societies (LAMPS) and support for Farmers’ Service Societies, including rural godown construction and managerial assistance. Industrial development initiatives focus on promotional activities, feasibility studies, and exploration of tea and other industries in preparation for the Sixth Plan period. Cultural preservation receives renewed attention through the establishment of a state-level cultural centre aimed at documenting indigenous Naga songs, dances, and folklore, while generating employment for educated youth.
Planning and Coordination Department Nagaland, Kohima December, 1977
Planning and Coordination Department Nagaland, Kohima December, 1977
Keywords: Nagaland Draft Annual Plan 1978–79; Agricultural Development; Land Reclamation; Minor Irrigation; Cooperation Structure; Large and Medium Industries; Art and Culture Preservation; Health Infrastructure; Urban Development; Town Planning; Rural Employment; Irrigation Potential